2020
DOI: 10.1002/adem.201901219
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Creep Resistance of an Ultrafine‐Grained Ti–6Al–4V Alloy with Modified Surface by Ion Implantation and (Ti + V)N Coating

Abstract: This research examines the creep behavior of an ultrafine‐grained (UFG) Ti−6Al−4V alloy processed by equal‐channel angular pressing followed by extrusion. It is shown that modifying the surface of the UFG alloy with nitrogen ions and then applying of a coating of (Ti + V)N inhibits the softening of the UFG alloy at temperatures up to 700 K due to a barrier effect in which the coating hinders the release of dislocations onto the surface. The differences in the mechanisms of crack initiation and failure of UFG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Recently, a similar dependence was observed on vacuum-plasma coatings deposited on UFG CP Ti as well as UFG titanium alloy Ti-6Al-4V. [5,6] It is obvious that the influence of the UFG structure on the hardness and adhesive strength of the coating is of common consistency. This effect can be due to the increase in the crystallization rate of the coating material and its vacuum-plasma deposition on the UFG substrate, resulting in the decrease in the grain/crystal size in the coating.…”
Section: Methodssupporting
confidence: 52%
See 4 more Smart Citations
“…Recently, a similar dependence was observed on vacuum-plasma coatings deposited on UFG CP Ti as well as UFG titanium alloy Ti-6Al-4V. [5,6] It is obvious that the influence of the UFG structure on the hardness and adhesive strength of the coating is of common consistency. This effect can be due to the increase in the crystallization rate of the coating material and its vacuum-plasma deposition on the UFG substrate, resulting in the decrease in the grain/crystal size in the coating.…”
Section: Methodssupporting
confidence: 52%
“…In addition to the technical regimes of the coating deposition, one of the main factors affecting the quality of the coating may be the structural state of the substrate material. [5,6] The study of the properties of a TiVN vacuum-plasma coating with vanadium layers on the samples of titanium alloy VT8M-1 conducted in this work demonstrated that substrate grain refinement directly influences the adhesive strength as well as physicomechanical properties of the coating.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations